Oleuropein Decreases Cyclooxygenase-2 and Interleukin-17 Expression and Attenuates Inflammatory Damage in Colonic Samples from Ulcerative Colitis Patients - Larussa, Tiziana (Nutrients, 2017)
Oleuropein (OLE) is the major phenolic secoiridoid of olive tree leaves, and its antioxidant and anti-inflammatory activities have been demonstrated in in vitro and in vivo animal models. The aim of this study was to investigate the activity of OLE in the colonic mucosa from patients with ulcerative colitis (UC). Biopsies obtained during colonoscopy from 14 patients with active UC were immediately placed in an organ culture chamber and challenged with lipopolysaccharide from Escherichia coli (EC-LPS) at 1 μg/mL in the presence or absence of 3 mM OLE. The expression of cyclooxygenase (COX)-2 and interleukin (IL)-17 was assessed in total protein extracts from treated colonic biopsies by Western blotting. Levels of IL-17 were also measured in culture supernatant by ELISA. A microscopic evaluation of the cultured biopsies was performed by conventional histology and immunohistochemistry. The expression of COX-2 and IL-17 were significantly lower in samples treated with OLE + EC-LPS compared with those treated with EC-LPS alone (0.80 ± 0.15 arbitrary units (a.u.) vs. 1.06 ± 0.19 a.u., p = 0.003, and 0.71 ± 0.08 a.u. vs. 1.26 ± 0.42 a.u., p = 0.03, respectively) as were the levels of IL-17 in culture supernatants of OLE + EC-LPS treated colonic samples (21.16 ± 8.64 pg/mL vs. 40.67 ± 9.24 pg/mL, p = 0.01). Histologically, OLE-treated colonic samples showed an amelioration of inflammatory damage with reduced infiltration of CD3, CD4, and CD20 cells, while CD68 numbers increased. The anti-inflammatory activity of OLE was demonstrated in colonic biopsies from UC patients. These new data support a potential role of OLE in the treatment of UC.